2021
DOI: 10.1101/2021.09.15.460487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetic Multiantigen MVA Vaccine COH04S1 Protects Against SARS-CoV-2 in Syrian Hamsters and Non-Human Primates

Abstract: Second-generation COVID-19 vaccines could contribute to establish protective immunity against SARS-CoV-2 and its emerging variants. We developed COH04S1, a synthetic multiantigen Modified Vaccinia Ankara-based SARS-CoV-2 vaccine that co-expresses spike and nucleocapsid antigens. Here, we report COH04S1 vaccine efficacy in animal models. We demonstrate that intramuscular or intranasal vaccination of Syrian hamsters with COH04S1 induces robust Th1-biased antigen-specific humoral immunity and cross-neutralizing a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
(94 reference statements)
1
8
1
Order By: Relevance
“…Several studies have reported that a recombinant MVA expressing the S protein induced protective immune responses in transgenic mice expressing human ACE2 and in non human primate (NHP) model [11][12][13][14] . More recently, a recombinant MVA expressing both the S and N proteins was shown to induce neutralizing antibody and cell-mediated immune responses 16 and was protective against SARS-CoV-2 challenge in hamsters and NHPs 17 . Although MVA is well known for its safety record and capacity to express foreign proteins, Its immunogenicity is lower than the first generation of VACV 27,[45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have reported that a recombinant MVA expressing the S protein induced protective immune responses in transgenic mice expressing human ACE2 and in non human primate (NHP) model [11][12][13][14] . More recently, a recombinant MVA expressing both the S and N proteins was shown to induce neutralizing antibody and cell-mediated immune responses 16 and was protective against SARS-CoV-2 challenge in hamsters and NHPs 17 . Although MVA is well known for its safety record and capacity to express foreign proteins, Its immunogenicity is lower than the first generation of VACV 27,[45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…Conserved T-cell epitopes in the N protein have been identified among SARS-CoV-2 variants and these epitopes may induce cross-protective immune responses against a wide range of emerging variants of SARS-CoV-2 50,51 . Several studies have demonstrated that the N protein vaccine candidates based on different platforms induced protection against SARS-CoV-2 infection 17,[52][53][54][55][56] . In this study, we constructed three novel rACAM2000 based COVID-19 vaccine candidates: rACAM2000S, rACAM2000N and rACAM2000SN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations